PEMETAAN KOMPONEN PENGELUARAN WISATAWAN DI KAWASAN WISATA TORAJA - Marigallang, Rhenaldy Arya; Pompeng, Olivia Devi Yulian; Marchelin, Marchelin (Sekolah Menengah Kejuruan (SMK) Pustek, 2024)
Toraja is a tourist area located in South Sulawesi province. Toraja is divided into two districts, Tana Toraja and North Toraja. Toraja has the charm of natural, traditional and cultural tourism that attracts foreign tourists and domestic tourists. In making a visit, these tourists certainly spend certain costs so that they can enjoy the tourism in Toraja. Tana Toraja and North Toraja district governments have not yet mapped the components of tourist expenditure on tourist expenditure while visiting Toraja. Data processing using the K-Means method. K-Means is a data maining method that provides a group description of an item. Tools used in data processing is RapidMiner application. The purpose of this study is to map or group the components of tourist expenditure in the Toraja tourism area. The results of this mapping there are 2 clusters formed, namely, cluster 0 which amounts to 79 and cluster 1 which amounts to 21, so that the results of this study can be used as a reference and benchmark for the Tana Toraja and North Toraja Regency governments and decision making for interested parties so as to improve the regional economy.